2000
DOI: 10.2170/jjphysiol.50.155
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Response during Incremental Exercise in Master Runners.

Abstract: Abstract:We analyzed the kinetics of heart rate (HR) response during incremental treadmill exercise in thirteen master runners (62Ϯ1 yr). The HR/running speed (HR/S ) relationship showed the existence of a point of downward deflection (HR d ) in only ϳ31% of the subjects.Resting echocardiographic evaluations showed similar heart dimensions in all of the subjects. In conclusion, HR does not seem to show a curvilinear response (downward deflection) in most aged athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(18 reference statements)
4
4
0
2
Order By: Relevance
“…In this study, we succeeded in identifying HR DP in nine of our runners, whereas the remaining three runners showed entirely linear HR response. These results support the findings of other investigators who documented that HR DP could not always be observed during an incremental exercise test even when the modified CT protocol was applied (24,25). Bourgois and Vrijens (8) and Bourgois et al (7), on the other hand, were able to detect HR DP in all of their subjects who were also submitted to the modified CT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we succeeded in identifying HR DP in nine of our runners, whereas the remaining three runners showed entirely linear HR response. These results support the findings of other investigators who documented that HR DP could not always be observed during an incremental exercise test even when the modified CT protocol was applied (24,25). Bourgois and Vrijens (8) and Bourgois et al (7), on the other hand, were able to detect HR DP in all of their subjects who were also submitted to the modified CT.…”
Section: Discussionsupporting
confidence: 89%
“…However, the small sample size is a common characteristic of the majority of the previous HR DP studies (7,8,17,18,(22)(23)(24). Another limitation of this study is the fact that runners did not repeat the modified CT to assess reliability of this test.…”
Section: Discussionmentioning
confidence: 94%
“…From a great number of tests performed in subjects of different performance levels and age there were a number of heart rate curves to be non regular which was in contrast to Conconi et al 1,21 In a study including a great number of young male students we showed three typical patterns of the heart rate performance curve, namely a regular pattern such as described for Conconi's test, a strictly linear time course without any deflection at all and, even more interesting, an inverted time course of the HRPC in 6-8% of healthy young male subjects without any differences in the lactate performance curve or other related performance variables. 17 This pattern was also found in master runners 20 and young healthy female subjects ( Figure 2); however, the number of inverted curves was found half of the male counterparts. 39 This inverted HRPC focused our attention as this pattern was similar to that typically seen in heart disease patients which gave rise to some speculations about pathophysiological (pre)conditions even in young trained and apparently healthy subjects.…”
Section: Physiological Backgroundsupporting
confidence: 65%
“…No physiological explanation rather than a methodological artifact of the phenomenon 15 No causal relationship of the heart rate deflection point and the lactate anaerobic threshold 13,14 No standard methods for AT determination were used for comparison by the Italian working group [3][4][5] No uniform time course of the heart rate performance curve and even curves without a deflection at all [16][17][18][19][20] In 1996 Conconi et al presented an update of the method and gave some comments and results to clarify some of the early questions and criticism. 21 However, there were a substantial number of papers refuting the method.…”
mentioning
confidence: 99%
“…In endurance-trained elderly men (i.e., master marathoners with a mean age of 62 y and a mean V Ç O 2max of 50 ml´kg ±1´m in ±1 ), AerT GE and AnT GE occurred at similar relative intensities than those reported in young endurance athletes, i.e. at~65 and~85% V Ç O 2max , respectively [71]. These findings might indicate that habituation to high degrees of effort enables higher maximal ergometric measurements and, consequently, lower relative values for AerT GE and AnT GE .…”
Section: Older Subjectsmentioning
confidence: 84%